2019
DOI: 10.7717/peerj.7241
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in skeletal organic matrix proteins of scleractinian corals associated with mixed aragonite/calcite skeletons under low mMg/Ca conditions

Abstract: Although coral skeletons generally comprise aragonite crystals, changes in the molar Mg/Ca ratio (mMg/Ca) in seawater result in the incorporation of calcite crystals. The formation mechanism of aragonite and calcite crystals in the scleractinian coral Acropora tenuis was therefore investigated by RNA-seq analysis, using early growth stage calcite (mMg/Ca = 0.5) and aragonite (mMg/Ca = 5.2)-based corals. As a result, 1,287 genes were up-regulated and 748 down-regulated in calcite-based corals. In particular, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
5
15
0
Order By: Relevance
“…3 ), coinciding with the lowest ocean Mg/Ca ratio during the Phanerozoic (<1 mol/mol). Culturing experiments have suggested that low-Mg seawater chemistry strongly affects the expression of genes related to coral skeletal formation and may trigger a change from aragonite to calcite mineralogy ( 33 ). Other experiments have demonstrated a physiologically controlled calcite-to-aragonite mineralogical switch triggered by changes in the growth solution Mg/Ca ratio ( 21 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 ), coinciding with the lowest ocean Mg/Ca ratio during the Phanerozoic (<1 mol/mol). Culturing experiments have suggested that low-Mg seawater chemistry strongly affects the expression of genes related to coral skeletal formation and may trigger a change from aragonite to calcite mineralogy ( 33 ). Other experiments have demonstrated a physiologically controlled calcite-to-aragonite mineralogical switch triggered by changes in the growth solution Mg/Ca ratio ( 21 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are secreted by the calicoblastic ectoderm (Puverel, Tambutté, Zoccola, et al, ; Yamashiro & Samata, ), serve to connect that cell layer to the pre‐existing skeleton (Clode & Marshall, , ), and pattern both the physical and chemical environment of the calcifying medium (Chen et al, ; Clode & Marshall, , ; Drake et al, ). The SOM allows coral aragonite precipitation even under calcite‐promoting conditions (Higuchi et al, ; Higuchi, Shirai, Mezaki, & Yuyama, ; Yuyama & Higuchi, ). The amino acid composition of the SOM proteins across Scleractinia is heavily biased toward aspartic and glutamic acids (Mass et al, ; Mitterer, ; Young, ), a phenomenon not observed for tissue protein complexes (Yamashiro & Samata, ).…”
Section: Skeletal Structure and Formationmentioning
confidence: 99%
“…1.5 to 5.2 mol/mol (Stolarski et al, ) and aragonite is still detected among calcite in modern Acropora spp. when reared at Mg/Ca = 0.5 mol/mol (Higuchi et al, , ; Yuyama & Higuchi, ). Furthermore, calcite‐promoting conditions in the Cretaceous seas (the lowest Mg/Ca in the Phanerozoic) did not dictate the CaCO 3 polymorph change in skeletons of corals that remained aragonitic through their entire fossil record (Janiszewska, Mazur, Escrig, Meibom, & Stolarski, ).…”
Section: Skeletal Structure and Formationmentioning
confidence: 99%
“…These observations were later corroborated by Higuchi et al (2014), who reported significant amounts of calcite in the skeleton of juvenile Acropora tenuis , albeit at lower m Mg: m Ca ratios compared to Ries (2006). More recently, Yuyama et al (2019) reported changes in gene expression in the scleractinian coral A. tenuis grown in Mg-depleted seawater. These included the up-regulation of several putative skeletogenic genes, suggesting that lower m Mg: m Ca elicits a response in the corals’ calcification machinery.…”
Section: Introductionmentioning
confidence: 99%
“…These included the up-regulation of several putative skeletogenic genes, suggesting that lower m Mg: m Ca elicits a response in the corals’ calcification machinery. However, since Yuyama et al (2019) only manipulated the Mg-content of the water leaving the calcium levels constant, the molecular response of corals to m Mg: m Ca ratios comparable to those observed during geological periods corresponding to Calcite Seas, when both the concentration of calcium and magnesium changed, remain unknown.…”
Section: Introductionmentioning
confidence: 99%